Volunteering as a Principle Trend in Today’s World - T. I. Zakharova; K. V. Sadykova; A. A. Lebedev (Вестник Российского экономического университета имени Г. В. Плеханова)
Nowadays volunteer organizations are becoming more and more popular, which promotes building the trend towards socially oriented business by implementation of corporate volunteering programs. The growth in volunteer projects number fosters volunteer centers emergence all over the world and a serious impact of volunteer projects motivates a deeper study of this phenomenon. It should be pointed out that at present society is going through an active stage of passing over from situational volunteering to more systematic and deliberate functioning. The authors show that this fact is connected with the global development of culture of corporate social responsibility in our country and in the world and therefore, with introduction of standards and principles of corporate social responsibility in the in-company environment of organizations.